2022
DOI: 10.1177/02724316221114091
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Stressful Life Events and Chinese Adolescents’ Mental Health: Examining Resilience, Peer Relationship, and Parenting as Moderators

Abstract: The current study examines intrapersonal characteristics or factors (i.e., resilience), peer (i.e., quality of peer relationships), and family processes (i.e., parental involvement, critical comparison) as potential risk and protective factors for mental health of Chinese adolescents during COVID- 19 pandemic. A total of 504 seventh-grade students (52% boys) and their caregivers in Beijing, China completed an online survey in September 2020. Youth reported experiencing various COVID-19-related stressful life e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Due to COVID-19, schools in Beijing were closed during the spring of 2020 and reopened in the fall of 2020. Part of the data from Wave 1 was used in a separate manuscript (Cheong et al, 2023). All 7th graders and their parents in the school were invited to participate in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to COVID-19, schools in Beijing were closed during the spring of 2020 and reopened in the fall of 2020. Part of the data from Wave 1 was used in a separate manuscript (Cheong et al, 2023). All 7th graders and their parents in the school were invited to participate in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Youth resilience has also been associated with fewer mental health problems (Lau et al, 2015). Moreover, a study with Chinese adolescents during COVID‐19 has shown that resilience serves as a psychological resource for coping with stressful life events and alleviating mental health difficulties (Cheong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, pandemic-related life events were also examined for their association with adolescents' mental health. Thus, changes in family life, financial difficulties, learning difficulties, and tense relationships with parents were found to be associated with the onset of psychopathological symptoms; in those cases, resilience or good relationships with peers were found to act as compensatory factors [14].…”
Section: Life-changing Events Their Measurement and Impact On Well-beingmentioning
confidence: 99%
“…As far as adolescents are concerned, the stressful life events during COVID-19 scale [14] assessed adolescents' experiences of stressful life events during the COVID-19 pandemic (e.g., "my family experienced financial pressure during the COVID-19 pandemic" and "during COVID-19 virtual learning, I had conflicts with my parents because I cannot balance virtual learning and entertainment").…”
Section: Life-changing Events Their Measurement and Impact On Well-beingmentioning
confidence: 99%
“…The outbreak of the COVID-19 pandemic had a huge impact on people’s lives. During this period, the countries’ economy ( Goodell, 2020 ) and energy ( Jiang et al, 2021 ; Szczygielski et al, 2022 ) were affected, companies’ performance suffered ( Shen et al, 2020 ), and individuals’ multiple interpersonal relationships ( Morelli et al, 2020 ; Qu et al, 2021 ; Chung et al, 2022 ; Su et al, 2022 ; Zhu et al, 2022 ; Afriat et al, 2023 ; Cheong et al, 2023 ), mental health status and well-being are also threatened ( Crabtree et al, 2021 ; Stieger et al, 2021 ; Tan et al, 2021 ; Negri et al, 2023 ). Results of a systematic review by Xiong et al (2020) indicate that during the COVID-19 pandemic, the general population in China, Spain, Italy, Iran, the United States, Turkey, Nepal, and Denmark experienced relatively high proportions of anxiety (6.33% to 50.9%), depression (14.6% to 48.3%)), post-traumatic stress disorder (7% to 53.8%), psychological distress (34.43% to 38%), and stress (8.1% to 81.9%).…”
Section: Introductionmentioning
confidence: 99%